2016
DOI: 10.1111/apa.13491
|View full text |Cite
|
Sign up to set email alerts
|

Formal training in general movement assessment is required to effectively evaluate infants with perinatal asphyxia in outpatient settings

Abstract: This study demonstrated the reliability of the GMA method in a busy multidisciplinary Danish paediatric outpatient setting, when assessors had been formally trained in the method and used it regularly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
(36 reference statements)
2
7
0
Order By: Relevance
“…There was substantial agreement between consensus decisions but only moderate agreement between all assessors. Our on-site consensus results agree with one study estimating GMA's inter-rater agreement in the fidgety period showing substantial agreement (12). However, another study found only moderate agreement (10) while a third showed almost perfect agreement (11).…”
Section: Inter-rater Reliability In Gmasupporting
confidence: 87%
See 1 more Smart Citation
“…There was substantial agreement between consensus decisions but only moderate agreement between all assessors. Our on-site consensus results agree with one study estimating GMA's inter-rater agreement in the fidgety period showing substantial agreement (12). However, another study found only moderate agreement (10) while a third showed almost perfect agreement (11).…”
Section: Inter-rater Reliability In Gmasupporting
confidence: 87%
“…(6)(7)(8) Studies of GMA inter-rater reliability during the fidgety movement period have been done with different methods and with various results. (9)(10)(11)(12) To our knowledge, there are no studies on inter-rater reliability of GMA films of high-risk infants evaluated by blinded assessors and recorded in a home setting by parents using a smartphone app.…”
Section: Introductionmentioning
confidence: 99%
“…Second, a few authors [28,29,30] proposed that the high predictive values of the GMA might be only achievable within the expert group closely linked to the GM Trust. In order to reach a generalizability of our findings, we therefore paid special attention to include several study sites outside the centers where GM Trust experts are involved.…”
Section: Introductionmentioning
confidence: 99%
“…However, GMs’ assessment (GMA) is often criticised for its subjectivity, as it has not been quantitatively addressed what the criteria are for a reduced motor repertoire and the degree fidgety movements. Reliability of GMA is excellent among very specialised and experienced professionals, but lower reliability has been reported for medical staff after a training course and several years of experience 5,6 . The requirement of ample experience to construct the inner criteria for abnormal movements by individual raters hampers a widespread clinical use of GMA.…”
Section: Introductionmentioning
confidence: 99%